2021
DOI: 10.1210/clinem/dgab039
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Vitamin D Deficiency is a Risk Factor for Postthyroidectomy Hypoparathyroidism: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Context Whether pre-operative vitamin D deficiency (VDD) contributes to post-operative hypoparathyroidism (hypoPT) risk is unknown. Objective To meta-analyze the best available evidence regarding the association between pre-operative vitamin D status and hypoPT risk. Data Sources: A comprehensive literature search was conducted in PubMed, CENTRAL and Scopus databases, up to October 31, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Several studies reported that low preoperative 25OHD was associated with postoperative hypoparathyroidism or hypocalcemia [11,[21][22][23]. Bove et al [11] analyzed clinical and lab data of 177 patients who underwent total thyroidectomy and found preoperative vitamin D deficiency (<25 ng/mL) was an independent risk factor in the development of hypocalcemia [24]. In contrast to the abovementioned studies, some studies found no significant association between preoperative 25OHD and postoperative hypoparathyroidism [9,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported that low preoperative 25OHD was associated with postoperative hypoparathyroidism or hypocalcemia [11,[21][22][23]. Bove et al [11] analyzed clinical and lab data of 177 patients who underwent total thyroidectomy and found preoperative vitamin D deficiency (<25 ng/mL) was an independent risk factor in the development of hypocalcemia [24]. In contrast to the abovementioned studies, some studies found no significant association between preoperative 25OHD and postoperative hypoparathyroidism [9,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Bove et al [ 11 ] analyzed clinical and lab data of 177 patients who underwent total thyroidectomy and found preoperative vitamin D deficiency (<25 ng/mL) was an independent risk factor in the development of hypocalcemia (OR: 14.8, 95% CI: 1.59–59.70, p = 0.012). Recently, a meta-analysis was published by Vaitsi et al [ 24 ] which included 39 observational studies of patients undergoing thyroidectomy with preoperative vitamin D status and postoperative hypoparathyroidism data. Patients with preoperative vitamin D deficiency demonstrated a higher risk for transient hypoparathyroidism compared with those with preoperative vitamin D sufficiency (RR: 1.92, 95% CI: 1.50–2.45, I 2 = 85%) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in their study with 30 patients (12 with vitamin D deficiency and 18 with normal vitamin D levels), Alkhalili et al (22) reported that preoperative vitamin D deficiency was associated with postoperative hypocalcemia. In a systematic review and meta-analysis of observational study, Konstantina et al reported that patients with preoperative vitamin D deficiency had an increased risk of transient hypoparathyroidism following thyroidectomy, while those with severe vitamin D deficiency had an increased risk of permanent hypoparathyroidism (28).…”
Section: Discussionmentioning
confidence: 99%
“…Because this is a representation of a real-world cohort, data regarding preoperative calcium levels, corrected or ionized calcium values, preoperative medication, or preoperative vitamin D levels were not consistent enough to allow for proper evaluation. This might have been worthwhile, since preoperative vitamin D deficiency has been identified as a possible risk factor of PH [ 28 ]. Moreover, as a result of the inclusion criteria of the present study, there is a lack of data from “controls”, so no conclusion can be drawn with regard to the association of postoperative PTH levels with the incidence of PH.…”
Section: Discussionmentioning
confidence: 99%